2006
DOI: 10.1037/0022-006x.74.5.887
|View full text |Cite
|
Sign up to set email alerts
|

Writing about the benefits of an interpersonal transgression facilitates forgiveness.

Abstract: The authors examined the effects of writing about the benefits of an interpersonal transgression on forgiveness. Participants (N = 304) were randomly assigned to one of three 20-min writing tasks in which they wrote about either (a) traumatic features of the most recent interpersonal transgression they had suffered, (b) personal benefits resulting from the transgression, or (c) a control topic that was unrelated to the transgression. Participants in the benefit-finding condition became more forgiving toward th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
293
2
19

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(324 citation statements)
references
References 57 publications
(98 reference statements)
10
293
2
19
Order By: Relevance
“…Although people may ''feel'' that they intentionally decide to forgive an offender, they may often not be aware of the situational cues that influence this seemingly volitional decision. At the same time, it should be recognised that previous research has suggested the role of deliberative processes in forgiveness, for example by demonstrating that more benign attributions regarding a partner's offensive act are associated with higher levels of forgiveness (Boon & Sulsky, 1997;Fincham, 2000;Finkel et al, 2002;McCullough et al, 2006). Hence, it is important to consider the respective roles of deliberative and automatic processes in forgiveness.…”
Section: Theoretical Implications: Deliberative and Automatic Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Although people may ''feel'' that they intentionally decide to forgive an offender, they may often not be aware of the situational cues that influence this seemingly volitional decision. At the same time, it should be recognised that previous research has suggested the role of deliberative processes in forgiveness, for example by demonstrating that more benign attributions regarding a partner's offensive act are associated with higher levels of forgiveness (Boon & Sulsky, 1997;Fincham, 2000;Finkel et al, 2002;McCullough et al, 2006). Hence, it is important to consider the respective roles of deliberative and automatic processes in forgiveness.…”
Section: Theoretical Implications: Deliberative and Automatic Processmentioning
confidence: 99%
“…Such attributions are then supposed to reduce the negative feelings associated with the offender, and to re-instigate goodwill and positive feelings towards the offender. Recent research by McCullough, Root, and Cohen (2006) demonstrated that participants who were instructed to write about personal benefits resulting from a transgression subsequently reported higher levels of forgiveness (compared to control conditions in which participants wrote about a topic unrelated to the offence or wrote about negative features of the offence). Writing about the benefits led to increased cognitive processing of the event (e.g., greater insight, clearer cause-and-effect relations, and so on), which in turn facilitated forgiveness.…”
mentioning
confidence: 99%
“…We selected at random 100 other participants and of those, 94 (31.5% males and 64.9% females; M age = 27.11, SD = 10.00) completed the TRIM-18-S to assess estimated two-week testretest reliability. (TRIM-18;McCullough et al, 2006). The TRIM-18 consists of 18 items that measure avoidance, revenge and benevolence motivations toward a particular offender for a particular offense (i.e., episodic forgiveness).…”
Section: Methodsmentioning
confidence: 99%
“…These subscales measure two negative dimensions of forgiveness. Afterwards, six items were added, making the TRIM-18 (McCullough & Hoyt, 2002;McCullough, Root, & Cohen, 2006). The new items assessed benevolence, one of the positive dimensions of forgiveness.…”
Section: Introductionmentioning
confidence: 99%
“…An example item is: "After hearing this explanation, I could forgive the railway company for the delay". Items for revenge, avoidance, and benevolence were adapted from the Transgression-Related Interpersonal Motivations Inventory (McCullough, Root, & Cohen, 2006). The tendency to take revenge was measured with three items (α= 0.88).…”
Section: Methodsmentioning
confidence: 99%